The Influence of Human Resources on Graduates of Shariah Economics Study Program of Sunan Ampel State Islamic University of Surabaya on Job Opportunities - Muh. Syaukin Muttaqin (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2020)
This is a field research to highlight the issue of the influence of human resources on graduates of Shariah Economics Study Program of Sunan Ampel State Islamic University of Surabaya on employment opportunities. This issue will be broken down into two fundamental problems, namely; first, is there any influence of human resources on the graduates of Shariah Economics Study Program of Sunan Ampel State Islamic University of Surabaya on employment opportunities? and second, how is the influence of human resources on graduates of Shariah Economics Study Program of Sunan Ampel State Islamic University of Surabaya on employment opportunities? Data is obtained through questionnaire to respondents in the year 2015-2017 with non-probability sampling techniques, namely incidental sampling technique. The results of this study indicate that human resources, economics, and demographics of the graduates of Shariah Economics Study Program of Sunan Ampel State Islamic University of Surabaya have a significant effect on employment opportunities.